Nonlinear hydrodynamics analysis of a submerged spherical point absorber with asymmetric mass distribution. (March 2020) - Meng, Fantai; Rafiee, Ashkan; Ding, Boyin; Cazzolato, Benjamin; Arjomandi, Maziar
Abstract: In previous work, a frequency-domain model was developed from linear potential theory to investigate the oscillation modes and efficiency of a single-tether 3 degree-of-freedom submerged spherical point absorber with asymmetric mass distribution (SPAMD). It was found that the trajectory of the device has a strong correlation with the performance of the wave energy converter. Specifically, the SPAMD can generate unique circular trajectories under long waves, producing up to 3 times power that of a generic single-tether point absorber (PA). However, this conclusion might not be valid for large buoy displacements due to increased nonlinear hydrodynamic effects (e.g. surface piercing, overtopping water, and vortex shedding). In this study, the trajectory of the SPAMD was analysed to determine the dominant nonlinear hydrodynamic effect that degrades the performance of a fully submerged system. The analysis was conducted in a numerical wave tank experiment (NWT), based on the Navier-Stokes equation and using the computational fluid dynamic toolbox OpenFOAM and the open-source library OLAFLOW for wave generation and absorption. The results obtained from NWT experiments show that surface piercing has the largest negative impact on the system's performance, which compromises the efficiency of the SPAMD by modifying the trajectory and dissipating energy. As a result, the efficiency of the SPAMD significantly decreases for long waves when surface piercing is most likely to occur, which implies that submerged point absorbers are less efficient than the floating ones in this scenario. Furthermore, although the performance of the SPAMD were significantly compromised due to the effect of surface piercing, the resulting power improvement in comparison to the submerged generic point absorber was still considerable for some wave periods. Highlights: Asymmetric mass distribution of spherical point absorber WEC improves efficiency. CFD results generally reflect results obtained using linear potential flow models. Optimal trajectory of submerged WEC compromised by surface piercing. Surface piercing reduces efficiency of symmetric mass WEC more than asymmetric WEC.